Perspectives on Instructional Improvement and Quality Mechanisms in Practice Teaching: An Interaction with Head Teachers - Jora, Man Bhadur; Basnet, Hom Bahadur (ILAM इलम, 2026)
This qualitative study identifies the effectiveness of quality assurance practices, policy implications, and barriers to strengthening school-university partnerships and reforming M.Ed. practice teaching. The participation in a participatory interaction program at Kailali Multiple Campus (KMC) was taken up by 10 head teachers who had previously worked with M.Ed.'s interns. Braun and Clarke's (2006) analysis of data from focus groups and reflective prompts, guided by semi-structured protocols on pre-observation conferences, post-lesson debriefs, and rubrics was validated through member checks, summaries, triangulation. Through extended placements, school partnerships, and mentorship, KMC helps students build confidence while addressing the gaps in theory-practice. The head teachers supported structured feedback but identified discrepancies in alignment between schools and trainees, advocating for joint leadership. Nevertheless, coordinated workshops, predetermined lessons, rubrics, and incentives such as time and monetary rewards are all necessary to balance personal development with other demands, including absence debriefing, conventional approaches that employ minimal ICT skills, short placements in six weeks. A practical lab model with collaborative logs, workshops, and collaboration institutionalizes observation, feedback, or planning are essential for developing effective and possible trained teachers. In practice teaching, student teachers again need to have ICT modules and acquire skills to improve digital fluency and engagement for their betterment in the pedagogical and professional development.